2015
DOI: 10.14503/thij-14-4373
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Criteria Most Accurately Distinguish Cardiac from Noncardiac Causes of Dyspnea

Abstract: Cardiopulmonary exercise testing provides oxygen pulse as a continuous measure of stroke volume, which is superior to other stress-testing methods in which systolic function is measured at baseline and at peak stress. However, the optimal peak oxygen pulse criterion for distinguishing cardiac from noncardiac causes of exercise limitation is unknown. In comparing several peak oxygen pulse criteria against the clinical standard of cardiopulmonary exercise testing, we retrospectively studied 54 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, another study reported that flattening of the O 2 P curve during exercise can only be used to detect extensive but not mild myocardial ischemia 6 . Moreover, a study on multivariate criteria in diagnosing cardiac causes of exercise limitation found that the O 2 P curve flattening pattern was not superior to predicted O 2 P% 4 . Despite these inconsistent clinical implications of O 2 P curve flattening, 16.6% of patients with COPD have ischemic heart disease 34 , which enhances the importance of this pattern.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, another study reported that flattening of the O 2 P curve during exercise can only be used to detect extensive but not mild myocardial ischemia 6 . Moreover, a study on multivariate criteria in diagnosing cardiac causes of exercise limitation found that the O 2 P curve flattening pattern was not superior to predicted O 2 P% 4 . Despite these inconsistent clinical implications of O 2 P curve flattening, 16.6% of patients with COPD have ischemic heart disease 34 , which enhances the importance of this pattern.…”
Section: Discussionmentioning
confidence: 97%
“…Reduced O 2 P with a plateau, or decreasing pattern 4 , 5 when approaching peak exercise has been attributed to cardiac dysfunction or myocardial ischemia in patients with cardiac impairment. Although the relationship between a flattened O 2 P curve and severity of myocardial ischemia is not linear 6 , O 2 P remains an indicator of training effect 7 , and a prognosticator of heart failure 8 11 and primary pulmonary hypertension 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, O 2 P curve pattern (O 2 PCP) is the trajectory of O 2 P during exercise, and therefore represents continuous monitoring of O 2 P. O 2 PCP is different in patients with obstructive airway disease and heart disease [ 7 ]. However, three types of O 2 PCP have been reported in patients with dyspnea [ 17 ] and COPD: plateau (P), decreasing (D), and increasing (I) types [ 18 ]. Furthermore, the P and D types are signs of cardiac dysfunction or myocardial ischemia in subjects with various heart diseases [ 17 , 19 , 20 ], and their presence should prompt additional cardiovascular work-up [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The peak oxygen pulse is an expression of peak VO 2 that by its nature corrects for HR and when further corrected for age, sex, and anthropometrics can differentiate cardiac from noncardiac causes of exercise intolerance [ 31 , 32 ]. The findings of the current study have implications, as the peak O 2 pulse is associated with risk for sudden cardiac death, fatal coronary heart disease, CVD, and all-cause mortality [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%